Acetabular rim extension using a personalized titanium implant for treatment of hip dysplasia in dogs: short-term results - Kwananocha, Irin; Magré, Joëll; Willemsen, Koen; Weinans, Harrie; Sakkers, Ralph J. B.; How, Thijs; Verseijden, Femke; Tryfonidou, Marianna A.; van der Wal, Bart C. H.; Meij, Björn P. (Frontiers in Veterinary Science, 2023)
The aim of this study was to evaluate the efficacy of an ACEtabular rim eXtension (ACE-X) using a novel personalized 3-dimensional printed titanium shelf implant to increase femoral head coverage and decrease laxity of the hip joint in dogs with symptomatic hip dysplasia (HD). Seven to 38-month-old dogs with clinical signs of coxofemoral joint subluxation and radiographic evidence of HD with no or mild osteoarthritis (OA) were included. The Norberg angle (NA), linear percentage of femoral head overlap (LFO), and percentage of femoral head coverage (PC) were investigated radiographically and with computed tomography (CT) before and after surgery. OA was graded (scores 0 - 3) according to the maximum osteophyte size measured on radiography and CT. Also, joint laxity (Ortolani) test results, gait analysis, and Helsinki chronic pain index (HCPI) questionnaire were obtained at various time points. Acetabular rim extension was performed in 61 hips of 34 dogs; NA, LFO and PC were significantly higher immediately postoperatively and at the 1.5- and 3-month follow-up examinations compared to preoperative values (p < 0.05). Osteophyte size gradually increased over time (p < 0.05). The OA score significantly increased between preoperatively and directly postoperatively, and between preoperatively and at 3-month follow-up (p < 0.05). The laxity test normalized in 59 out of 61 hips after surgery and the HCPI questionnaire showed that the pain score decreased significantly at 1.5- and 3-month, postoperatively. Force plate showed no significant improvement during the 3 months follow up. In conclusion, ACE-X using a personalized shelf implant in young dogs with hip laxity due to symptomatic HD increased femoral head coverage and eliminated subluxation of the dysplastic hip joint in the short term. Further studies are required to study the long-term efficacy on gait, chronic pain and progression of osteoarthritis.